Purification and characterization of a sarcoplasmic serine proteinase from threadfin bream Nemipterus virgatus muscle. (30th June 2019) - Liu, Jin-Yang; Yoshida, Asami; Gao, Yi-Li; Shirota, Kazuya; Shiina, Yasuhiko; Noguchi, Erika; Kuwahara, Koichi; Osatomi, Kiyoshi
Highlights: A sarcoplasmic serine proteinase (SSP) was purified from threadfin bream muscle. The SSP was estimated to be 43.5 kDa by SDS-PAGE under non-reducing condition. The optimum pH and temperature of the SSP was 9.5 and 50 °C, respectively. N -terminal amino acid sequence of the SSP was determined as IVGGYEXQPYSQAHQVSLNSGY. The SSP was considered as a modori -inducing proteinase. Abstract: A sarcoplasmic serine proteinase (SSP) was purified from threadfin bream ( Nemipterus virgatus ) belly muscle by ammonium sulfate precipitation and a series of chromatographies including Q-Sepharose, Phenyl Sepharose and Superdex 200. The SSP was purified 1967 folds with a yield of 4.8%. The molecular weight of the SSP was estimated to be 43.5 kDa and 22.5 kDa on SDS-PAGE under non-reducing and reducing conditions, respectively. The N -terminal amino acid sequence of the two protein bands were determined as IVGGYEXQPYSQAHQVSLNSGY and corresponded. It is suggested that the SSP exists as a homodimer. Optimum pH and temperature were 9.5 and 50 °C, using Boc-Val-Pro-Arg-MCA as a substrate. Substrate specificity and effects of inhibitors indicated that the SSP was a trypsin-like serine proteinase. The SSP was responsible for hydrolyzing myosin heavy chain (MHC) and inducing modori phenomenon in the threadfin bream surimi gel. Thus, the SSP was considered as a modori -inducing proteinase.